The impact of dronedarone on patients with atrial fibrillation and diabetes – a sub-analysis of the ATHENA and EURIDIS/ADONIS trials. (14th October 2021) - Handelsman, Y; Steinberg, B; Rodbard, H; Bunch, J; Thind, M; Bigot, G; Konigsberg, L; Wieloch, M; Bhattacharyya, N; Kowey, P
Abstract: Background: Diabetes is a well-established risk factor for the development of atrial fibrillation (AF), and is associated with worse outcomes. Both the ATHENA (NCT00174785) and EURIDIS (NCT00259428)/ADONIS (NCT00259376) were randomized, double-blind, placebo-controlled clinical trials, that evaluated dronedarone 400 mg BID vs placebo (2:1 ratio) in patients with AF and atrial flutter (AFL). The aim of this post-hoc analysis was to evaluate the efficacy and safety of dronedarone in patients with or without diabetes. Methods: Patients from the ATHENA trial with diabetes, and from the EURIDIS/ADONIS trials with diabetes, >1 elevated glucose level during trial (unfasted ≥11; fasted ≥7 mmol/L) or presence of diabetes medications were identified and categorized according to diabetes status at baseline. Descriptive analyses of baseline characteristics in patients with and without diabetes receiving dronedarone or placebo were assessed, and time to occurrence of the primary outcomes, CV hospitalization or death in ATHENA and AF/AFL recurrence within 12 months in EURIDIS/ADONIS, were estimated using the Kaplan–Meier method. Log-rank test was used to assess the statistical differences of the survival curves. Results: A total of 945 (20.4%; dronedarone [N=482], placebo [N=463]) patients of 4628 patients in ATHENA, and 215 (17.4%; dronedarone [N=148], placebo [N=67]) of 1237 patients in EURIDIS/ADONIS had type 2 diabetes. Patients with diabetes were more likely to have coronary heart disease, hypertension, or structural heart disease in both trials. In ATHENA, there were higher rates of CV hospitalization or death in patients with diabetes (39.5%) than without (34.7%). The proportion of patients with diabetes with first CV hospitalization or death was lower with dronedarone versus placebo (35.1 vs 44.1%) and the time to first event occurred significantly later with dronedarone than placebo (log-rank p=0.005; Figure 1). In ATHENA, median time to first AF/AFL recurrence occurred significantly later with dronedarone vs placebo consistently in patients with diabetes (722 vs 527 days; log-rank p=0.004) or without diabetes (741 vs 492 days; log-rank p<0.001). In EURIDIS/ADONIS, the median time to first AF/AFL recurrence occurred later with dronedarone versus placebo in both patients with diabetes (100 vs 23 days; log-rank p non-significant) and without (120 vs 59 days; log-rank p<0.001; Figure 2). Occurrence of any treatment-emergent adverse event [TEAE] (ATHENA: 74.9 vs 71.2%; EURIDIS/ADONIS: 77.7 vs 68.1%) and serious TEAEs (ATHENA 23.8 vs 18.9%; EURIDIS/ADONIS 25.7 vs 18.5%) with dronedarone were similar for patients with or without diabetes. Conclusion: Diabetic patients had shorter time to AF recurrences and higher rates of CV hospitalization than patients without diabetes. Dronedarone was equally safe, decreasing the risk of CV hospitalization or death, and effective, delaying AF/AFL recurrences, in patients with and without diabetes. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Sanofi